L’émergence de surfeurs malgaches à Madagascar : comment de nouvelles spatialités participent aux façonnements de paysages - Lilia Khelifi (Projets de Paysage)
Based on a qualitative field study conducted during one month in 2017 on the emergence of surfing in the three Eastern coastal regions of Mahambo, Ambatomalama and Fort-Dauphin in Madagascar, I propose to explore the landscape dimensions generated by surfers. Through their corporeal experience of the shoreline, which englobes the beach and the waves, surfers immerse themselves in a singular environment in the practice of their sport. The temporalities of the waves and the spatialities of the people in the survey are prior conditions of existence to the landscape. The field of social and cultural geography enables us to investigate the representations and the spatial and social practices expressed by the surfers interviewed. The paradoxical relationship with the coastline shifting between attraction and rejection, provides food for thought regarding what may constitute a landscape for individuals or social groups. The recent dissemination of surfing practices and the imaginary dimension sheds light on the local contexts encountered.